The effectiveness and cost-effectiveness of assistive technology and telecare for independent living in dementia: a randomised controlled trial. (23rd January 2021) - Howard, Robert; Gathercole, Rebecca; Bradley, Rosie; Harper, Emma; Davis, Lucy; Pank, Lynn; Lam, Natalie; Talbot, Emma; Hooper, Emma; Winson, Rachel; Scutt, Bethany; Ordonez Montano, Victoria; et al.
Abstract: Objectives: The use of assistive technology and telecare (ATT) has been promoted to manage risks associated with independent living in people with dementia but with little evidence for effectiveness. Methods: Participants were randomly assigned to receive an ATT assessment followed by installation of all appropriate ATT devices or limited control of appropriate ATT. The primary outcomes were time to institutionalisation and cost-effectiveness. Key secondary outcomes were number of incidents involving risks to safety, burden and stress in family caregivers and quality of life. Results: Participants were assigned to receive full ATT (248 participants) or the limited control (247 participants). After adjusting for baseline imbalance of activities of daily living score, HR for median pre-institutionalisation survival was 0.84; 95% CI, 0.63 to 1.12; P  = 0.20. There were no significant differences between arms in health and social care (mean -£909; 95% CI, -£5, 336 to £3, 345, P  = 0.678) and societal costs (mean -£3, 545; 95% CI, -£13, 914 to £6, 581, P  = 0.499). ATT group members had reduced participant-rated quality-adjusted life years (QALYs) at 104 weeks (mean − 0.105; 95% CI, −0.204 to −0.007, P  = 0.037) but did not differ in QALYs derived from proxy-reported EQ-5D. Discussion: Fidelity of the intervention was low in terms of matching ATT assessment, recommendations and installation. This, however, reflects current practice within adult social care in England. Conclusions: Time living independently outside a care home was not significantly longer in participants who received full ATT and ATT was not cost-effective. Participants with full ATT attained fewer QALYs based on participant-reported EQ-5D than controls at 104 weeks.